One, two, three: How many green patents start bringing financial benefits for small, medium and large firms? - Anastasia Semenova; Konstantin Semenov; Maxim Storchevoy (Economies, 2023)
This paper studies the relationship between environmental innovations and firms' financial performance from the perspective of environmental activism intensity. We explore how the number of green patents affects the financial performance of small, medium, and large firms and whether the growing number of green patents positively affects firms' financial performance. We employed a panel data sample of 1136 green innovative and 2395 non-green innovative firms from the USA and Europe and compared their financial results. The results show that small firms benefit financially only in the second year after the first green patent implementation. Medium-sized firms enjoy improved financial performance in the first two years after the implementation of one or two green patents; however, the third green patent does not anyhow improve the financial performance. Large firms gain financial benefits every year after issuing green patents regardless of the patents' quantity. Generally, the increase in financial performance is moderate in the first year, reaches the maximum in the second year, and becomes statistically insignificant in the third year after the last green patent's implementation.
Keywords: 330; environmental innovations; financial performance; green patents; sustainable development